Financial Return on Equity (FROE) as a new extended DuPont analysis, applied to industrial companies in Chile - Joseli, William (2021)
In 2020, Arana publishes an article in which he proposes an extended Dupont Analysis from a financial perspective applied to industrial companies listed on the Lima Stock Exchange. Based on this research, it was proposed to apply the same methodology to the Chilean context. The objective of the article is to define what are the elements that a DuPont analysis should have, not from an accounting point of view, but from a financial perspective, starting from three elements: asset turnover, profit margin and financial leverage. For this purpose, the data of 38 industrial companies listed on the Santiago Stock Exchange (Chile) from 2014 to 2019 were analyzed. The methodology used was multiple linear regression for the main elements of a DuPont analysis focused on finance or Financial Return on Equity (FROE). The value of this research lies in its contribution to scientific knowledge by delving into financial models and providing a new and useful tool for business decision making.